(untitled) (Revista cientifica In Vestigium Ire, 2020)
This article presents a review of the proposal of the current U.S. President Donald Trump, regarding the construction of a wall on the frontier with the United Mexican States in order to abolish ilegal immigration into the United States, lower crime rates and other problems they face because of illegal immigrants as expressed by the U.S. President and his decision to declare a National Emergency to comply with his proposal. It also presents different points of view together with a possible responsibility that the United States could assume with such a decision and a real problem that goes beyond illegal immigration.